Impact Of The Quality Of Front Office Services To The Consumer Satisfaction Level Sinar Sport Hotel Bengkulu - Sari, Ida Permata; Narti , Sri; Octaviani , Vethy (CV. Era Digital Nusantara, 2024)
The study aims to analyze the impact of the quality of front office services on the level of consumer satisfaction at Sinar Sport Hotel Bengkulu. The approach used is quantitative with survey methods. The total population of 92 respondents was random sampling technique of 48 respondents with sample determination technique using Slovenian formula. Using a questionnaire that covers independent variables of service quality and dependent variables is the consumer satisfaction rate of a survey instrument of up to 40 respondents. The validity and reliability test results show that the research instrument is valid and reliable. Further, the data was analyzed using a t test through the SPSS 26 application. Variables of service quality influenced consumer satisfaction on Sinar Sport Hotel Kota Bengkulu. Based on the calculation of the above t test obtained the variable value of service quality of 7.420 and Sig. value of 0,000, whereas for the ttable value of the total number of respondents 48 is the value of 1,683. Therefore, the computation obtains by comparing between the thitung value > ttable is 7,420 greater than 1,683 and the Sig value < 0,05 is 0,000 smaller than 0,05 so that the hypothesis of Ho is rejected and Ha is accepted. It can be concluded that service quality variables influence consumer satisfaction of guests at Sinar Sport Hotel Kota Bengkulu.